A variável ambiental no planejamento de eventos turísticos : estudo de caso da Festa Nacional da Uva - RS - Pereira, Gisele Silva (My University, 2015)
An event needs to work out the environmental variable during all planning’s phases in order to accept its environmental responsibility. This present research plans to examine the established relationships between the environmental variable and a tourist event. Therefore, the subject of research originated from the following question: is the environmental variable considered when planning the National Grape Festival 2006? With this in mind, the objective of this study is to identify the consideration given to the environmental variable when planning the National Grape Festival 2006, which happened in Caxias do Sul – RS – Brazil. Along with the general objective, the following specific objectives are pointed out: a) to check the established relationships between environmental information and the Festival’s planning; b) to identify how solid waste produced at the Festival is handled; c) to examine the solid waste prevention principle at the Festival’s planning; d) to identify environmental education actions at the Festival’s planning; e) to examine water, eletric power and residuary water’s variables at the Festival’s planning; f) to check environmental criterion consideration when choosing the Festival’s sponsors and exhbitors. In an effort to meet the objectives suggested, direct observation was carried out regarding the Grape Festival at two different periods of time. On top of that, 19 people were interviewed, including the chairman, vice-chairman and the directors of the Festival’s organizing commitee. The interview script consisted of questions concerning: a) environmental practices; b) solid waste; c) Festival’s advertising; d) sponsors and exhbitors; e) parades; f) local Olympic Games; g) water; h) power; i) residuary water (sewage). Through the results obtained in the research, we are able to conclude that there are many environmental actions introduced in an isolated manner at the Festival. However it is important to build a new planning concept for it, which might effectively include the environmental variable. With regards to it, undergraduate courses such as tourism, hotel management and stricto sensu tourism have responsibility for developing studies which consider the environmental variable. As it was possible to conclude through the research, there are many relationships yet to be established between the environmental variable and tourist events’ planning. Therefore, a new look at tourist events, planning them under an environmental view, is essencial.
Para que um evento assuma sua responsabilidade ambiental, é preciso que o mesmo contabilize a variável ambiental em todas as fases de seu planejamento. A presente investigação propõe-se a examinar as relações estabelecidas entre a variável ambiental e um evento turístico. Assim, o problema de pesquisa decorre da seguinte indagação: a variável ambiental é considerada no planejamento da Festa Nacional da Uva 2006? Nesse sentido, o objetivo deste estudo é identificar a consideração da variável ambiental no planejamento da Festa Nacional da Uva 2006, realizada na cidade de Caxias do Sul, no Estado do Rio Grande do Sul. Aliados ao objetivo geral, destacam-se os seguintes objetivos específicos: a) verificar as relações estabelecidas entre a informação ambiental e o planejamento da Festa da Uva; b) identificar as condições de manejo dos resíduos sólidos gerados na Festa da Uva; c) examinar o princípio da prevenção da geração de resíduos sólidos no planejamento da Festa da Uva; d) identificar ações de educação ambiental no planejamento da Festa da Uva; e) examinar as variáveis água, energia elétrica e água residuária no planejamento da Festa da Uva; f) verificar a consideração do critério ambiental na escolha dos patrocinadores e expositores da Festa da Uva. Para atender aos objetivos propostos, foram realizadas observações diretas no âmbito da Festa da Uva, em dois momentos distintos. Também foram entrevistados 19 sujeitos, os quais correspondem ao presidente, aos vicespresidentes e aos diretores das comissões organizadoras da Festa da Uva. As perguntas que compõem o roteiro de entrevista relacionam-se: a) às práticas ambientais; b) a resíduos sólidos; c) à divulgação da Festa; d) aos expositores e patrocinadores; e) aos desfiles; f) às olimpíadas coloniais; g) à água; h) à energia; i) à água residuária (esgoto). Os resultados obtidos com a pesquisa permitem concluir que existem ações ambientais implantadas de forma isolada na Festa da Uva. Entretanto, é importante construir um novo conceito de planejamento para a Festa da Uva, em que se contemple efetivamente a variável ambiental. Nesse sentido, cabe aos cursos de graduação em turismo e hotelaria e aos cursos stricto sensu em turismo desenvolverem estudos que contemplem a variável ambiental. Como foi possível constatar com a realização da pesquisa, ainda há relações que precisam ser estabelecidas entre a variável ambiental e o planejamento de eventos turísticos. Cabe, portanto, um novo olhar aos eventos turísticos, planejando-os sob a ótica ambiental.
Keywords: Turismo cultural; Avaliação de riscos ambientais; Festa da Uva - Caxias do Sul (RS); Festas folclóricas; Heritage tourism; Environmental risks assessment; Grape Festival - Caxias do Sul (Brazil); Folk festivals